Psychometric properties of the shortened and rescaled versions of the Job Security Index and Job Security Satisfaction scale. Issue 2 (16th May 2022) - Bazzoli, Andrea; Probst, Tahira M.
Abstract: The psychometric properties of two shortened and rescaled versions of widely used measures of job insecurity were evaluated. Using survey data from 292 US working adults and relying on classical test theory, confirmatory factor analysis, and item response theory analyses, results indicated that these new versions had high reliability and similar psychometric properties compared with the original versions. Empirical evidence further established favorable convergent and discriminant validity, based on the revised scales' relationships with relevant covariates. The revised versions also showed substantially improved precision of measurement over a broader range of cognitive and affective job insecurity levels (i.e. they provide greater information for a wider range of participants experiencing varying levels of insecurity). These results indicate the briefer rescaled versions should be preferred over the original scales.